Spatial Distribution, Seasonal Dynamics, and Sex Ratio of Lycorma delicatula (Hemiptera: Fulgoridae) Adults on Tree of Heaven. (30th August 2022) - Liu, Houping; Hunter, Matthew
Abstract : The spatial distribution and seasonal dynamics of the spotted lanternfly ( Lycorma delicatula ) on tree of heaven ( Ailanthus altissima ) were studied in Pennsylvania through weekly sampling of 30 trees (6 sites, 5 trees/site) from 27 July to 8 November 2020. Adults found on each tree were separated into six within-tree positions (lower trunk, middle trunk, upper trunk, first branch, second branch, and above second branch) by four directions (East, South, West, and North). In total, 78, 796 adults were counted at the six study sites during the 15-week period. Significant differences in total adult count were found among trees, with a mean of 2, 627 (254–12, 023) adults/tree. Study site, tree diameter, and cardinal direction had no significant impact on adult spatial distribution. However, significantly more adults were found on the middle (1077), the lower (865), and the upper trunk (337) compared with the first (194), the second (93), and above second branches (60). Most adults were congregated on the lower and middle trunks. Seasonal dynamics followed adult development and migration patterns in the field, with peak populations observed in weeks 35 (24–30 August) and 37 (7–13 September) before declining. Female-based sex ratios ranged from 77.3 to 100% according to weekly monitoring of the lower 1 m trunk of 10 trees at 2 sites (5 trees/site) for 12 weeks from 17 August to 8 November, with 7, 356 females and 197 males counted, respectively. Impact factors such as attack patterns, intraspecific congregation, adult seasonality, and sexual dimorphism in host selection are discussed.